2018
DOI: 10.1093/pubmed/fdy082
|View full text |Cite
|
Sign up to set email alerts
|

Association of e-cigarette use with oral health: a population-based cross-sectional questionnaire study

Abstract: In a population-based health survey of US adults, self-reported health behavior and outcomes, daily use, but not intermittent use of e-cigarettes was independently associated with poor oral health. Care must be exercised in seeking 'healthier' cigarette alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
1
28
0
5
Order By: Relevance
“…There have been a few studies that address the direct health effect of e-cigs usage, especially regarding the oral cavity. In a cross-sectional analysis, it is reported that daily e-cig usage was associated with significantly increased odds of permanent loss of any tooth from nontraumatic causes in adults in the USA and it was indicated that vaping may be a risk factor for poor oral health outcomes including periodontal disease and tooth loss [73]. An association between e-cigs usage and higher odds of cracked/broken teeth, pain in the tongue and/or inside-cheek as compared to those who had never used e-cigs, among adolescents was previously shown [74].…”
Section: Studies On Direct Health Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…There have been a few studies that address the direct health effect of e-cigs usage, especially regarding the oral cavity. In a cross-sectional analysis, it is reported that daily e-cig usage was associated with significantly increased odds of permanent loss of any tooth from nontraumatic causes in adults in the USA and it was indicated that vaping may be a risk factor for poor oral health outcomes including periodontal disease and tooth loss [73]. An association between e-cigs usage and higher odds of cracked/broken teeth, pain in the tongue and/or inside-cheek as compared to those who had never used e-cigs, among adolescents was previously shown [74].…”
Section: Studies On Direct Health Effects Of Ends In the Oral Cavitymentioning
confidence: 99%
“…However, another study showed a statistically significant increase in gingival inflammation in tobacco smokers who switched from smoking to vaping for two weeks [22]. A larger cross-sectional analysis using the 2016 Behavioral Risk Factor Surveillance System survey data showed an increased odds of teeth loss due to decay or gum disease with the use of e-cigarettes [23].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the viscous aerosol and oral cavity is of particular interest for several reasons: (i) dental professionals have long been aware of the danger of tobacco products and nicotine on oral health, (ii) the oral cavity which includes lips, gingiva, teeth, palate and tongue is the first organ to directly interact with the e-cigarette aerosol, (iii) changes in tissue surface characteristics from eating glutinous food (e.g., caramels, licorices, or sour candies) and high sucrose intake (e.g., sodas) can lead to negative health consequences in oral cavity. Many e-liquids share similar physical and chemical properties to sugary and gelatinous foods that have been proven to be major risks for dental caries [ 30 , 31 ], and recently (iv) a population-based cross-sectional study revealed that daily use of e-cigarettes is independently associated with poor oral health [ 32 ].…”
Section: Introductionmentioning
confidence: 99%